STRATEGI KOMUNIKASI CROWDFUNDING PADA KOLASE.COM - Venessa Agusta Gogali; Fajar Muharam; Syarif Fitri (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2019)
Crowdfunding is a new method in fundraising activities based online. Moreover, the level of penetration of social media to the community is increasingly high. This makes social activists and academics realize that it is important to study social media communication strategies in crowdfunding activities. There is encouragement to provide an overview of crowdfunding activities. So the author conducted a research on